Special issue - Industrial engineering: Overcoming the crisis. CIO2012 - Jesús García-Arca; J.Carlos Prado-Prado (Journal of Industrial Engineering and Management (JIEM), 2013)
This special issue of the Journal of Industrial Engineering and Management contains a selection of the papers that were accepted at the CIO2012 International Conference, developed in Vigo (Spain) under the motto "Industrial Engineering: Overcoming the Crisis". CIO 2012 gives continuity to the series of annual Conferences initiated in September 1986 in La Rábida (Huelva, Spain). This conference is a very significant scientific event in Business & Operations Management and related areas. Researchers, academics, scientists and managers of diverse parts of the world have the opportunity to exchange experiences, new ideas and topics, in those fields related to Industrial Engineering. The 6th International Conference addresses the great multidisciplinary field formed by Industrial Engineering, from an international point of view. The papers here presented cover a number of consolidated and emerging topics of the conference scope and they may help readers to gain a deeper understanding of how Industrial Engineering could contribute to overcome the economic crisis. We would like to express our gratitude to all the authors, reviewers and the Organizing Committee for their enthusiastic work and magnificent support during CIO 2012.
Keywords: 650; CIO2012; special issue; crisis